Endophyte-Mediated Resistance in Tomato to Fusarium oxysporum Is Independent of ET, JA, and SA - Constantin, Maria E.; de Lamo, Francisco J.; Vlieger, Babette V.; Rep, Martijn; Takken, Frank L. W. (Frontiers in Plant Science, 2019)
Root endophytes can confer resistance against pathogens by direct antagonism or via the plant by triggering induced resistance. The latter typically relies on jasmonic acid (JA) /ethylene (ET)-depended signaling pathways, but can also be triggered via salicylic acid (SA)-dependent signaling pathways. Here, we set out to determine if endophyte-mediated resistance (EMR), conferred by the Fusarium endophyte Fo47, against Fusarium wilt disease in tomato is mediated via SA, ET, JA. To test the contribution of SA, ET and JA in EMR we performed bioassays with Fo47 and Fusarium oxysporum f.sp. lycopersici in tomato plants impaired in SA accumulation (NahG), JA biosynthesis (def1) or ET-production (ACD) and -sensing (Nr). We observed that the colonization pattern of Fo47 in stems of wildtype plants was indistinguishable from that of the hormone mutants. Surprisingly, EMR was not compromised in the JA, ET or SA compromised mutant lines. The independence of EMR on SA, JA and ET implies that this induced resistance response against Fusarium wilt disease is distinct from the classical ISR response, providing exciting possibilities for control of wilt diseases not reliant on conventional defense pathways.